A 3D combined particle-element method for intense impulsive loading computations involving severe distortions. (October 2015) - Johnson, G.R.; Beissel, S.R.; Gerlach, C.A.
Abstract: This article presents a Combined Particle-Element Method (CPEM) for 3D intense loading computations that include severe distortions. It includes the numerical algorithms and example computations. The advantages of this method are that the lower-strained particles (stress points) are computed with a fast and accurate finite-element formulation, and the higher-strained particles are computed with a meshless-particle formulation that can handle severe distortions. Furthermore, the meshless-particle algorithm (with MLS strain rates and weak-form forces) is consistent and does not exhibit tensile instabilities. It is also well suited for conversion of finite elements into variable-connectivity meshless particles because the conversion does not require deletion of elements and addition of particles. Instead there is simply a branch point based on equivalent plastic strain. The basic approach can also be used for the element algorithm only or the particle algorithm only. Highlights: CPEM provides favorable characteristics of both finite elements and meshless particles. CPEM allows for accurate simulations of mild structural deformations as well as severe distortions. CPEM computations can be run with elements only, particles only, or conversion of distorted elements into particles.